The rise in unemployment - Bean, C (Blackwell, 1986)
Fourteen papers presented at a conference on rising unemployment held at the White House Conference Centre, Chelwood Gate, Sussex, in May 1985. Specific topics include aggregate supply and demand factors in OECD unemployment; wage policies and adjustments; the divergence of unemployment rates; productivity; and industrial unemployment. Case studies are drawn from Australia; Austria; Belgium; Great Britain; Canada; the United States; France; West Germany; Italy; Japan; the Netherlands; and Spain. Bean and Layard are at the London School of Economics. Nickell is at Nuffield College, Oxford. Author and subject indexes.